PENGARUH KOMPETENSI DAN INDEPENDENSI AUDITOR TERHADAP KUALITAS AUDIT DENGAN INTEGRITAS SEBAGAI VARIABEL MODERASI PADA KANTOR AKUNTAN PUBLIK KOTA MEDAN - Tina, Agus (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
This study aims to determine, test and analyze empirically about the effect of competence and independence to audit quality which is moderated by integrity at Public Accountant Firm in Medan. This study is quantitative study with associative approach. The objects of this research are the auditors who work in Public Accounting Firm in Medan. The sampling technique used in this research was proporsional random sampling with a sample size of 60 respondents from a total population of 150 respondents.. The data collection technique was carried out by distributing questionnaires. While the data analysis technique is using by structural equation model partial least square (SEM-PLS) which is processed using Smart PLS statistical software. The results showed that the Competence has no effect on audit quality at Public Accountant Firm in Medan. But integrity could moderated the effect of competence to audit quality at Public Accountant Firm in Medan. The independence gave effect on audit quality at Public Accountant Firm in Medan. Independence gave effect on audit quality that moderated by integrity at Public Accountant Firm in Medan.